Unprecedented isolation of a dinuclear tin (II) complex stabilized by pyridine‐2, 6‐dimethanol: structure, DFT and in vitro screening of cytotoxic properties. (29th May 2019) - I., Mantasha; Raza, Md Kausar; Shahid, M.; Ansari, Azaj; Ahmad, Musheer; Khan, Ishaat M.
Abstract : In this work, we report a novel dinuclear Sn (II) complex, [Sn2 (Hpdm)2 (H2 O)6 ] 2H2 O 2Cl (1 ) (H2 pdm = pyridine‐2, 6‐dimethanol), which has been crystallized out and characterized by elemental analysis, FTIR, 1 H and 13 C NMR, single crystal X‐ray studies and Density Functional Theory (DFT) analysis. X‐ray structure of1 has confirmed it to be a dinuclear alkoxo‐bridged Sn (II) species where each metal adopts a seven coordinate distorted pentagonal bipyramidal (pbp) geometry. This is the first hepta‐coordinated Sn (II) complex ever isolated apart from already reported stannylenes. Spin density plots from DFT support the +2 oxidation state of each tin metal. Hirshfeld surface analysis reveals the presence of various H‐bonding interactions in the molecule and molecular docking results along with DFT confirm higher binding affinity of the present complex towards DNA. Moreover, the complex exhibits promising anticancer activities against HeLa and A549 cancer cell lines. Abstract : An unusually stabilized dinuclear Sn (II) species has been crystallized out, characterized by spectral, X‐ray and DFT analysis and evaluated for anticancer properties. The complex exhibits promising activities against cervical (HeLa) and lung (A549) cancer cell lines.